2016
DOI: 10.1590/0104-6632.20160332s20140209
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Modelling of the Filling Process of Hydrogen Onboard Vehicle Cylinders

Abstract: -Complete modelling of the filling process occurring in a hydrogen-fueled vehicle storage cylinder is examined. A simultaneous modelling of the flow and heat transfer within the cylinder and cylinder wall has not been considered in previous studies. Rapid filling may result to an unexpected temperature rise and breaching of the safety standards. In the present study, initially a correlation was developed based on a numerical simulation for predicting the heat transfer rate between in-cylinder flow and the cyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The results obtained align with findings from prior studies [24,[26][27][28][29]52]. The initial mass flow rate for methane is 0.053 kg/s, and for pure hydrogen, it is 0.016 kg/s, with a final pressure in the tank of 35 MPa.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The results obtained align with findings from prior studies [24,[26][27][28][29]52]. The initial mass flow rate for methane is 0.053 kg/s, and for pure hydrogen, it is 0.016 kg/s, with a final pressure in the tank of 35 MPa.…”
Section: Resultssupporting
confidence: 87%
“…The maximum mass flow rate is observed with pure methane (Sample 1), whereas the lowest is observed for pure hydrogen (Sample 4), owing to the higher density of methane compared to hydrogen. The results obtained align with findings from prior studies [24,[26][27][28][29]52]. The initial mass flow rate for methane is 0.053 kg/s, and for pure hydrogen, it is 0.016 kg/s, with a final pressure in the tank of 35 MPa.…”
Section: Resultssupporting
confidence: 87%
“…Despite the interest in the modelling of cylinder filling with compressed natural gas, there are also studies which have considered thermodynamic parameters during hydrogen fast filling to cylinders (types III and IV) [32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the vehicle's hydrogen‐storage cylinder during discharge was anticipated and calculated by Molkov et al [ 28 ] Zhang et al [ 29 ] employed a thermodynamic technique to calculate the hydrogen‐filling process of a 70 MPa/100 L vehicle's hydrogen‐storage cylinder. Deymi et al [ 30 ] discovered that the ambient temperature influences the filling process, namely the ultimate hydrogen temperature and filling quality. Roberta Caponi et al [ 31 ] analyzed the cost of five types of hydrogen with a capacity of 100–400 kg d −1 HRS, and the analysis showed that the cost of the on‐site hydrogen production HRS was about 11–12 EUR kg −1 , while the cost of the external delivery HRS was 8–9 EUR kg −1 .…”
Section: Introductionmentioning
confidence: 99%